The Improved Prognosis of Hypoplastic Left Heart: A Population-Based Register Study of 343 Cases in England and Wales - Best, Kate E.; Miller, Nicola; Draper, Elizabeth; Tucker, David; Luyt, Karen; Rankin, Judith (Frontiers in Pediatrics, 2021)
Background Hypoplastic Left Heart Syndrome (HLHS) is a severe congenital heart defect (CHD) characterised by the underdevelopment of the left side of the heart with varying levels of hypoplasia of the left atrium, mitral valve, left ventricle, aortic valve and aortic arch. Accurate survival estimates play a crucial role in counselling parents following diagnosis. The aim of this study was to report survival estimates up to age 15 for children born with HLHS or hypoplastic left ventricle with additional CHD in England and Wales. Methods Cases of HLHS or hypoplastic left ventricle with additional CHD notified to four congenital anomaly registers in England and Wales during 1998-2012, matched to Office for National Statistics mortality information, were included. Kaplan-Meier survival estimates to age 15 were reported. Cox regression models were fitted to examine risk factors for mortality. Results There were 244 cases of HLHS and 99 cases of hypoplastic left ventricle co-occurring with other CHD, with traced survival status. Kaplan-Meier survival estimates for HLHS were 84.4% at age one week, 76.2% at one month, 63.5% at age one year, 58.6% at age five years, 54.6% at age 10 years and 32.6% to age 15 years. The Kaplan-Meier survival estimates for cases of hypoplastic left ventricle co-occurring with additional CHD were 90.9% at age one week, 84.9% at one month, 73.7% at age one year, 67.7% to age five years, 59.2% to age 10 years and 40.3% to age 15 years. Preterm birth (p=0.007), low birth weight (p=0.005), and female sex (p=0.01) were associated with mortality. Conclusions We have shown that prognosis associated with HLHS in the 21st century exceeds that of many previous population-based studies, likely due to improvements in intensive care technologies and advances in surgical techniques over the last few decades.